1995
DOI: 10.1016/s0140-6736(95)91743-8
|View full text |Cite
|
Sign up to set email alerts
|

Mutated methylenetetrahydrofolate reductase as a risk factor for spina bifida

Abstract: The following full text is a publisher's version. For additional information about this publication click this link.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
426
5
28

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 779 publications
(487 citation statements)
references
References 8 publications
28
426
5
28
Order By: Relevance
“…Given the established protective effects however, of folic acid supplementation on the occurrence and reoccurrence of NTD, polymorphisms in genes encoding the proteins that are directly involved in folate metabolism, uptake and transport have been investigated. The reduced activity of the MTHFR enzyme in individuals with the MTHFR 677TT genotype, decreases the availability of 5-methyltetrahydrofolate which plays a key role in methylation (10) and decreases global DNA methylation (63,64) ; therefore, it is no surprise that this specific mutant gene has been extensively investigated as a genetic risk factor for NTD (65,66) . Over the past two decades, several reports have shown a 2 to 4-fold increased risk of NTD if the infant or the mother has the MTHFR 677TT genotype (65,(67)(68)(69)(70) .…”
Section: The Role Of the Mthfr 677c T Polymorphism In Neural Tube Defmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the established protective effects however, of folic acid supplementation on the occurrence and reoccurrence of NTD, polymorphisms in genes encoding the proteins that are directly involved in folate metabolism, uptake and transport have been investigated. The reduced activity of the MTHFR enzyme in individuals with the MTHFR 677TT genotype, decreases the availability of 5-methyltetrahydrofolate which plays a key role in methylation (10) and decreases global DNA methylation (63,64) ; therefore, it is no surprise that this specific mutant gene has been extensively investigated as a genetic risk factor for NTD (65,66) . Over the past two decades, several reports have shown a 2 to 4-fold increased risk of NTD if the infant or the mother has the MTHFR 677TT genotype (65,(67)(68)(69)(70) .…”
Section: The Role Of the Mthfr 677c T Polymorphism In Neural Tube Defmentioning
confidence: 99%
“…The reduced activity of the MTHFR enzyme in individuals with the MTHFR 677TT genotype, decreases the availability of 5-methyltetrahydrofolate which plays a key role in methylation (10) and decreases global DNA methylation (63,64) ; therefore, it is no surprise that this specific mutant gene has been extensively investigated as a genetic risk factor for NTD (65,66) . Over the past two decades, several reports have shown a 2 to 4-fold increased risk of NTD if the infant or the mother has the MTHFR 677TT genotype (65,(67)(68)(69)(70) . van der Put et al (71) reported an even higher risk of an NTD pregnancy if both the mother and the fetus were homozygous for the MTHFR 677C T polymorphism.…”
Section: The Role Of the Mthfr 677c T Polymorphism In Neural Tube Defmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Reduced enzymatic activity has been observed in TT677 or CC1298 homozygotes, and to a lesser extent in heterozygous individuals. 4,6,7 The role of MTHFR variants in a number of disorders, involving disturbances in folate metabolism, such as neural tube defects (NTDs), 8 vascular disease 9,10 and cancer susceptibility, is well documented. 11,12 Recently, the potential role of these polymorphisms in response to MTX treatment has been addressed in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…This mutation can be regarded as a genetic risk factor for spina bifida and supports the hypothesis of defective folate metabolism in at least a subset of mothers with neural tube defects. 24 Cystathionine synthesase abnormalities can also raise homocysteine and this has also been reported in a minority of patients with neural tube defects. 25 Overcoming an abnormality in homocysteine metabo lism, particularly an abnormality of methionine synthase by folic acid supplementation, is presently the favoured postulated mechanism of action of folic acid.…”
Section: Mechanism Of Action Of Folic Acidmentioning
confidence: 96%